A Hypomorphic Allele of Aryl-hydrocarbon Receptor-associated-protein-9 Produces a Phenocopy of the Ahr Null - Lin, Bernice C. (2008)
The aryl hydrocarbon receptor associated protein-9 (ARA9) is a chaperone of the aryl hydrocarbon receptor (AHR). The AHR has been shown to play a late developmental role in the normal closure of a fetal hepato-vascular shunt known as the ductus venosus (DV). Given that Ara9 null mice display early embryonic lethality, we generated a hypomorphic Ara9 allele (designated Ara9(fxneo)) that displays reduced ARA9 protein expression. In an effort to demonstrate the role of ARA9 protein in AHR-mediated DV closure, we used combinations of Ara9 wildtype (Ara9(+/+)), null (Ara9(−/−)) and hypomorphic (Ara9(fxneo)) alleles to produce mice with a graded expression of the ARA9 protein. Liver perfusion studies demonstrated that while none of the Ara9(+/+) mice displayed a patent DV, the shunt was observed in 10% of the Ara9(+/fxneo) mice, 55% of the Ara9(+/−) mice and 83% of the Ara9(fxneo/fxneo) mice. The fact that expression level of ARA9 correlates with the frequency of a phenocopy of the Ahr null allele supports the conclusion that the ARA9 protein is essential for AHR signaling during development.